Detection of Lead (Pb) and Cadmium (Cd) Concentrations and Hazards in Some Baby Food Samples - Fadhel, Jabbar Faleh; Ghathwan, Maha (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study was conducted to detect the concentration of lead and cadmium in baby foods, (18) samples were examined, which are the most available from various local markets in the city of Baghdad (at a rate of (9) samples of baby food consisting of cereals and (9) samples of baby foods consisting of vegetables). All samples were examined using an atomic flame absorptiometry (AAS-7000), all results showed the presence of lead and cadmium and the highest concentration value of lead in baby foods consisting of cereals (1.0986) and cadmium in baby foods consisting of vegetables (0.0015) ppm. Lead exceeded 100% limitations and cadmium did not exceed that. The results reported on the risks of contamination, as the mean daily intake (g/kg/d) for lead (1.3538) and cadmium amounted to (0.010), and the target hazard quotient index was high for the index (THQ>10) for lead in most of the samples examined and reached (THQ